Pengaruh Penerapan Sistem Pengendalian Internal dan Sistem Informasi Akuntansi Berbasis Artificial Intelligence Terhadap Kecenderungan Fraudulent Financial Reporting (Studi Empiris Pada Hotel Berbintang di Bali) - Pratama, Jordy; Julianto, I Putu (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
This study aims to determine the effect of the application of an internal control system and the application of an artificial intelligence-based accounting information system to the tendency of fraudulent financial reporting in hotels. This type of research is a quantitative research which has a research sample of 70 respondents, the sampling technique used is purposive sampling and the data is obtained by distributing questionnaires online through google form media. The data used are primary data in the form of respondents' answers and processed using SPSS version 21 for windows devices, and the results show that the application of an internal control system and the application of an artificial intelligence-based accounting information system negatively affects the tendency of fraudulent financial reporting in hotels.